Dampak Pandemi Terhadap Kinerja Proyek Konstruksi Industri di Indonesia - Intan Permatasari; Iva Mindhayani (Program Studi Teknik Industri Universitas Setia Budi, 2024)
The Covid-19 outbreak has caused economic downturns and recession. In 2021, Covid-19 cases in Indonesia has a significant increase. The construction sector in Indonesia faced substantial challenges due to the pandemic, evidenced by contracted growth. The impact of the Covid-19 pandemic on the construction industry cannot be viewed solely from an economic perspective but must consider various factors. Issues in the construction industry affect project performance. Previous research could not interpret the relationship between individual pandemic impacts and project performance levels. Therefore, this study aims to determine factors Covid-19 pandemic affects construction project performance in Indonesia. The study identifies five factors that may influence project performance: (1) challenges in implementing social distancing, (2) movement restrictions, (3) challenges of working from home (WFH), (4) planning for worker limitations, and (5) use of personal protective equipment (PPE). Data was collected using questionnaires distributed to project managers in the construction industry. Primary analysis was conducted using Partial Least Square (PLS). The results indicate that three variables significantly impact project performance in the construction industry. The level of movement restrictions during the pandemic (lockdown) and the planning for worker limitations negatively affect project performance, while movement restrictions positively affect the challenges of implementing social distancing.